Global media ethics problems and perspectives - Ward, Stephen J. A. (Stephen John Anthony) 1951- (Chichester, West Sussex Wiley-Blackwell, 2013)
"Global Media Ethics is the first comprehensive cross-cultural exploration of the conceptual and practical issues facing media ethics in a global world. A team of leading journalism experts investigate the impact of major global trends on responsible journalism. The first full-length, truly global textbook on media ethics; Explores how current global changes in media promote and inhibit responsible journalism; Includes relevant and timely ethical discussions based on major trends in journalism and global media; Questions existing frameworks in media ethics in light of the impact of global media; Contributors are leading experts in global journalism and communication "-- Provided by publisher.
Machine generated contents note: Introduction: Media Ethics as Global Stephen Ward, University of Wisconsin-Madison Section One: Media ethics worldwide 1. Why Media Ethics Still Matters Nick Couldry, Goldsmiths, University of London 2. Universals and Differences in Global Journalism Ethics Thomas Hanitzsch, Patrick Lee Plaisance, and Elizabeth A. Skewes 3. The Only Way is Ethics: The Role of the Journalist in Reporting International Conflicts Howard Tumber, City University, London 4. Global Journalism Networks: Funding and Ethical Hurdles Brant Houston, University of Illinois Section Two: Media and diverse public spheres 5. Contextual Ethics and Arab Mass Media Ralph Berenger & Mustafa Taha, American University in Sharjah, UAE 6. From Journalism Ethics to an Ethics of Citizenship: Evidence from Colombia Hernando Rojas and Tim Macafee, University of Wisconsin-Madison 7. Media Ethics in a New Democracy: South African Perspectives on Freedom, Dignity and Citizenship Herman Wasserman, Rhodes University, South Africa 8. Democratization by Boilerplate: National Media, International Norms, and Sovereign National Building in a Post-War Liberia Jo Ellen Fair, University of Wisconsin-Madison Section Three: Global issues 9. The Role of Global Media in Telling the Climate Change Story Sharon Dunwoody and Magda Konieczna, University of Wisconsin-Madison 10. Ethics of Global Disaster Reporting: Journalistic Witnessing and Objectivity Karin Wahl-Jorgensen, Cardiff School of Journalism and Mervi Pantti, University of Helsinki 11. Affective Expertise: The Journalism Ethics of Celebrity Sourcing Katherine Bell, University of Washington, Seattle 12. Global Media Ethics, Justice, and Indian Journalism Shakuntala Rao, State University of New York, Plattsburgh Section Four: Theoretical foundations 13. Global Media Ethics? Issues, Requirements, Challenges, Resolutions Charles Ess, Aarhus University, Denmark 14. Global Ethics and the Problem of Relativism Clifford Christians, University of Illinois-Urbana 15. Global Media Ethics: Utopian or Realistic? Stephen J. A. Ward, University of Wisconsin-Madison .
Keywords: Journalistic ethics; Mass media -- Moral and ethical aspects